A clinical case of secondary xanthomatosis in a patient with biliary cirrhosis - N. V. Zilberberg; I. A. Kuklin; M. M. Kokhan; G. D. Safonova; O. G. Rimar; N. P. Toropova; P. S. Gileva; I. D. Kuznetsov (Лечащий Врач)
The article describes the clinical manifestations of secondary xanthomatosis in a 46-year-old patient with primary biliary cirrhosis who was consulted by a dermatovenerologist. The diagnosis was confirmed by pathomorphological studies of the of skin biopsies.Xanthomatosis is a systemic disease that develops with lipid metabolism disorders (primary and secondary hyperlipoproteinemia) and is characterized by local or generalized deposition in lipid tissues with the formation of xanthomas — nodules of a white or yellowish tint. Disorders of lipid metabolism are an essential component of the pathogenesis of primary biliary cirrhosis, when serum cholesterol accumulation is observed during obstruction or hypoplasia of the biliary tract. Along with the formation of flat xanthomas, patients may experience jaundice, hyperpigmentation, and itching of the skin. Flat xanthomas are clinically manifested in the form of clearly delimited plaques of yellow-orange or flesh tones, measuring up to 3–5 cm or more, slightly rising above the skin, with a smooth or wrinkled surface. Typical localization is the skin of the trunk, hips, buttocks, face, neck, folds of the palms and fingers.The presented clinical observation indicates that the appearance of flat xanthomas in the patient was the first sign of metabolic disorders, and a sharp deterioration of the skin process was a consequence of the progression of the pathology of the hepatobiliary system.The importance of clinical alertness of doctors in relation to concomitant diseases occurring with disorders of lipid metabolism is emphasized.